Exploring Adaptation to Climate Change in Agriculture : The Potential of Cross-Sectional Analysis - Mendelsohn, Robert; Dinar, Ariel (World Bank, Washington, DC, 2012)
Scientists are confident of a link between greenhouse gas emissions, the increasing concentration of those gases in the atmosphere, and climate change. However, the final impacts from climate change are difficult to estimate, since we have no direct experience with new climates. Past climate change has been small and slow, making the impacts hard to discern. Further, technological changes have obscured signals from historic climate changes. Despite these difficulties, the impact literature has made many strides toward understanding and quantifying climatic impacts.